2017
DOI: 10.1080/17435390.2017.1343874
|View full text |Cite
|
Sign up to set email alerts
|

Oral subchronic exposure to silver nanoparticles causes renal damage through apoptotic impairment and necrotic cell death

Abstract: Silver nanoparticles (AgNPs) are one of the most widely used nanomaterials. Following oral exposure, AgNPs can accumulate in various organs including kidneys where they show gender specific accumulation. There is limited information on their effect on renal system following long-term animal exposure especially at the ultramicroscopic and molecular level. In this study, we have assessed the effect of 60 days oral AgNPs treatment on kidneys of female Wistar rats at doses of 50 ppm and 200 ppm that are below prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 69 publications
2
29
0
Order By: Relevance
“…Changes in blood parameters indicated by a significant elevation of ALT, AST, and hepatoxicity, shown by histological damages (necrosis, hepatocytic inflammation, and the resultant aggregation of lymphocytes in liver tissue) were also observed in a study that evaluated the toxic effect of 14 days of oral exposure to AgNPs (40 nm) at doses 20 and 50 ppm in BALB/C mice [176]. Moreover, Tiwari et al [177] determined the effect of 60 days AgNPs (10-40 nm) treatment on the kidneys of female Wistar rats at doses of 50 and 200 ppm, and they demonstrated significant mitochondrial damage, increased levels of serum creatinine, and early toxicity markers such as KIM-1, clusterin and osteopontin. Abbreviations: lung (Lu), liver (Li), spleen (Sp), kidney (Ki), brain (Br), heart (Ht), bladder (Bl), uterus (Ut), thymus (Th), cecum (Ce), placenta (Pl), polyvinylpyrrolidone (PVP), and citrate (CT).…”
Section: N/a [166]mentioning
confidence: 83%
“…Changes in blood parameters indicated by a significant elevation of ALT, AST, and hepatoxicity, shown by histological damages (necrosis, hepatocytic inflammation, and the resultant aggregation of lymphocytes in liver tissue) were also observed in a study that evaluated the toxic effect of 14 days of oral exposure to AgNPs (40 nm) at doses 20 and 50 ppm in BALB/C mice [176]. Moreover, Tiwari et al [177] determined the effect of 60 days AgNPs (10-40 nm) treatment on the kidneys of female Wistar rats at doses of 50 and 200 ppm, and they demonstrated significant mitochondrial damage, increased levels of serum creatinine, and early toxicity markers such as KIM-1, clusterin and osteopontin. Abbreviations: lung (Lu), liver (Li), spleen (Sp), kidney (Ki), brain (Br), heart (Ht), bladder (Bl), uterus (Ut), thymus (Th), cecum (Ce), placenta (Pl), polyvinylpyrrolidone (PVP), and citrate (CT).…”
Section: N/a [166]mentioning
confidence: 83%
“…For example, AgNPs treatment of osteoblasts decreases their viability and inhibits their differentiation. [6c] As previously reported, oral AgNPs treatment at the dose of 200 ppm could also cause weight decrease and loss of kidney function in a rat model . In another study, Kim et al reported that high‐dose (500 mg kg −1 d −1 ) AgNPs intake could cause significant liver damage in both male and female rats, with 125 mg kg −1 d −1 being considered as the lowest observable adverse‐effect level of AgNPs oral toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The increased level of creatinine in the serum of the experimental animals treated with NiNPs may refer to the affected kidney functions, such as the glomerular filtration rate, which may be due to the accumulation of NiNPs in the kidney. Such increase in serum creatinine level was observed after exposure to other nanoparticles such as sliver NPs (Tiwari et al, 2017).…”
Section: Discussionmentioning
confidence: 67%